Optimal harvesting policy of a prey–predator model with Crowley–Martin-type functional response and stage structure in the predator - Dubey, Balram; Agarwal, Shikhar; Kumar, Ankit (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, a three-dimensional dynamical model consisting of a prey, a mature predator, and an immature predator is proposed and analysed. The interaction between prey and mature predator is assumed to be of the Crowley–Martin type, and both the prey and mature predator are harvested according to catch-per-unit-effort (CPUE) hypothesis. Steady state of the system is obtained, stability analysis (local and global both) are discussed to explore the long-time behaviour of the system. The optimal harvesting policy is also discussed with the help of Pontryagin’s maximum principle. The harvesting effort is taken as an effective control instrument to preserve prey and predator and to maintain them at an optimal level.